The associations among emotional factors, personality traits, and addiction‐like eating: A study on university students in six Asian countries/regions. Issue 2 (16th May 2020) - Tang, Catherine So‐kum; Gan, Yiqun; Ko, Jenny; Kwon, Jung‐hyde; Wu, Anise; Yan, Elsie; Yogo, Masao
Abstract: Objective: Addiction‐like eating (AE) is characterized by food cravings and loss of control over excessive food consumption. This study investigated the associations among emotional factors, personality traits, and AE symptoms in Asian young adults. Method: This study included 6, 823 Asian university students in South Korea, China, Singapore, Hong Kong/Macao, Japan, and Taiwan. Participants completed the modified Yale Food Addiction Scale (mYFAS) and scales on the Big‐Five personality traits, impulsivity, anxiety, and depression. Results: 6.2% of the participants met the mYFAS (DSM‐IV‐TR) food addiction diagnostic threshold. Participants from South Korea (7.9%) had the highest rate of food addiction, while participants from Japan (5.1%) and Taiwan (4.1%) reported the lowest rates. Emotional factors of anxiety and depression were the most robust correlates of AE symptoms, followed by country/region and personality factors of higher impulsivity, higher extraversion, and lower agreeableness. Personality correlates were region‐specific. Higher impulsivity was a significant correlate for participants from South Korea and Taiwan, higher extraversion for participants from Singapore and Japan, and lower agreeableness for participants from China and Taiwan. Gender was also a significant correlate for participants from South Korea, Hong Kong/Macao, and Taiwan. Discussion: Emotional and personality factors are important correlates of AE symptoms among Asian young adults.